Paraneoplastic Pemphigus: Paraneoplastic Autoimmune Disease of the Skin and Mucosa - Kim, Jong Hoon; Kim, Soo-Chan (Frontiers in Immunology, 2019)
Paraneoplastic pemphigus is a rare but life-threatening mucocutaneous disease mediated by paraneoplastic autoimmunity. Various neoplasms are associated with paraneoplastic pemphigus. Intractable stomatitis and polymorphous cutaneous eruptions, including blisters and lichenoid dermatitis, are characteristic clinical features caused by humoral and cell-mediated autoimmune reactions. Autoreactive T cells and IgG autoantibodies against heterogeneous antigens, including plakin family proteins and desmosomal cadherins, contribute to the pathogenesis of paraneoplastic pemphigus. Several mechanisms of autoimmunity may be at play in this disease on the type of neoplasm present. Diagnosis can be made based on clinical and histopathological features, the presence of anti-plakin autoantibodies, and underlying neoplasms. Immunosuppressive agents and biologics including rituximab have been used for the treatment of paraneoplastic pemphigus; however, the prognosis is poor due to underlying malignancies, severe infections during immunosuppressive treatment, and bronchiolitis obliterans mediated by autoimmunity. In this review, we overview the characteristics of PNP and focus on the immunopathology and the potential pathomechanisms of this disease.